Enteral nutrition is associated with improved outcome in patients with severe sepsis. A secondary analysis of the VISEP trial. - Elke, G.; Kuhnt, E.; Ragaller, M.; Schadler, D.; Frerichs, I.; Brunkhorst, F. M.; Loffler, M.; Reinhart, K.; Weiler, N. (Med Klin Intensivmed Notfmed, 2013)
INTRODUCTION: The optimal nutritional strategy remains controversial, particularly in severely septic patients. Our aim was to analyze the effect of three nutritional strategies--enteral (EN), parenteral (PN), and combined nutrition (EN+PN)--on the outcome of patients with severe sepsis or septic shock. PATIENTS AND METHODS: This secondary analysis of the prospective, randomized-controlled, multicenter "Intensive Insulin Therapy and Pentastarch Resuscitation in Severe Sepsis (VISEP)" trial only included patients with a length of stay in the intensive care unit (ICU) of more than 7 days. Besides patient characteristics, data on nutrition therapy were collected daily for up to 21 days. Morbidity as measured by the mean Sequential Organ Failure Assessment (SOFA) score, incidence of secondary infections, renal replacement therapy, ventilator-free days and severe hypoglycemia, length of ICU stay, and mortality at 90 days were compared between the three nutritional strategies. RESULTS: In all, 353 patients were included in the analysis with the majority (68.5 %) receiving EN+PN, 24.4 % receiving EN, and only 7.1 % receiving PN. Median caloric intake was 918 kcal/day (EN), 1,210 kcal/day (PN), and 1,343 kcal/day (EN+PN; p < 0.001). In the latter group, calories were predominantly administered via the parenteral route within the first week. The rate of death at 90 days was lower with EN than with EN+PN (26.7 % vs. 41.3 %, p = 0.048), as was the rate of secondary infections, renal replacement therapy, and duration of mechanical ventilation. In the adjusted Cox regression analysis, the effect on mortality [hazard ratio (HR)= 1.86, 95 % confidence interval (CI): 1.16-2.98, p = 0.010] and the rate of secondary infections (HR= 1.89, 95 % CI: 1.27-2.81, p = 0.002) remained different between EN and EN+PN. CONCLUSION: In patients with severe sepsis or septic shock and prolonged ICU stay, EN alone was associated with improved clinical outcome compared to EN+PN. This hypothesis-generating result has to be confirmed by a randomized-controlled trial in this specific patient population.
Keywords: APACHE; Abdomen/surgery; Aged; Combined Modality Therapy; *Critical Care; Energy Intake; *Enteral Nutrition; Female; Gastrointestinal Diseases/surgery; Germany; Humans; Hydroxyethyl Starch Derivatives/*therapeutic use; Insulin/*therapeutic use; *Intensive Care Units; Length of Stay; Male; Middle Aged; *Parenteral Nutrition, Total; *Plasma Substitutes; Postoperative Complications/therapy; Proportional Hazards Models; Prospective Studies; Renal Replacement Therapy; Respiration, Artificial; Sepsis/mortality/*therapy; Shock, Septic/mortality/*therapy; Survival Rate